Fault modelling based on local magnetic anomaly data in geothermal prospect area Rajabasa Lampung - IKA DARUWATI (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Two and half dimensions fault modelling was conducted based on Local Magnetic Anomaly Data in Mount Rajabasa site, Lampung. The research utilized total magnetic anomaly secondary data to perform quantitative interpretation. The total magnetic anomaly data was then transformed into flat field, reduced to a pole and carried upward continuation until at an altitude of 4000 MSL to separate local anomaly and regional anomaly. Based on the qualitative interpretation of the anomalous magnetic field, it indicates a normal fault with the direction of northeast – southwest and northwest – southeast. In the research, quantitative interpretation was done to local anomaly by selecting two locations that showed the presence of lineament patterns in the contour. Modelling was conducted by using Mag2DC software. By modelling those two sites, was obtained that fault model that is located in Mount Rajabasa area is a normal fault trending northwest – southeast with the value of magnetic susceptibility contrast of 0.004 and -0.015 in cgs units